Response of the Thermosphere‐Ionosphere System to an X‐Class Solar Flare: 30 March 2022 Case Study - Volkan Sarp; Erdal Yiğit; Ali Kilcik (Space Weather)
Abstract The response of the thermosphere ionosphere system to an X1.3 class solar flare is studied using observations of the total electron content (TEC) and the Global Ionosphere Thermosphere Model (GITM) simulations. The solar flare erupted from the active region AR12975 on 30 March 2022. Owing to the absence of accompanying severe geomagnetic activity, it was possible to isolate the effects of the flare on the upper atmosphere. TEC data are processed for Continental USA (CONUS), employing filtering and binning techniques to create 2D variation maps. The spectral content of the TEC variations is analyzed using a wavelet coherence method. The immediate response of the solar flare exhibited broad similarities, while notable differences were observed during the recovery period between the East and West sides of the CONUS. GITM is used to explore the East–West asymmetry of the key T‐I parameters. Simulation results reveal that the coinciding interplanetary magnetic field southward turning had a greater influence on these parameters compared to the solar flare, while their nonlinear interaction introduced complex variations. Additional investigation reveals gravity wave damping also contributes to the asymmetric solar flare response.